Annual Plan 1995-96 Tripura State Part I (Writeup) Planning and Coordination Department - Planning Commission (Planning Commission, 1995)
For some age group categories, the percentage population distribution is in excess of the percentage distribution for the preceding age groups. For example, in 1961 the age groups 20-24, 25-29, 60-64 and 70 + recorded a higher distribution than the immediate preceding age groups. Similar is the pattern during 1971 for the age groups 35-39, 60-64, 70 + and during 1981 for the age groups 60-64, 70 +. Such abnormal increase in distribution of population cannot be accounted for by natural growth and can only be explained by immigration. The population distribution in Tripura, in the age groups of 0-4 during 1971 and 0-9 during 1981 shows a lower percentage distribution than the corresponding figures for the country as a whole. Thus, a faster decline in Birth Rates had begun in Tripura as compared to the country as early as 1971. That the population grew at a faster pace than the whole country is explained by reason other than natural growth i.e. immigration. The above observations deserve consideration whi1e cha1 king out a strategy for population control in Tripura. The density of population in Tripura has gradually picked up with the National figures. As per 1991 census, Tripura with 267 persons per Sq.Km. of land area was the 16th most dense state in the country and the most densely habitated state in the North Eastern Region after Assam (density per Sq.Km.286).
Write-up
Government of Tripura